ECONOMIC DEVELOPMENT IN TIMES OF JUSTICE: THE THIRD WAVE OF ACCESS TO JUSTICE, MEDIATION, CONCILIATION AND THE ROLE OF THE PUBLIC DEFENDER'S OFFICE - Almeida, Daniela Marques do Amaral (Seven Editora, 2026)
This article investigates the right of access to justice and the main obstacles that hinder its realization, with a special focus on the theory of "waves of reform" proposed by Mauro Cappelletti and Bryant Garth (1988). The analysis concentrates on the third wave, which incorporates self-composition practices such as mediation and conciliation. The central objective of the research is to demonstrate how mediation, conciliation, and the extrajudicial actions of the Public Defender's Office contribute to expanding access to justice and promoting economic development. To this end, a qualitative methodological approach is adopted, with a theoretical and exploratory profile, based on current legislation and specialized legal literature. Additionally, a quantitative approach will be used, through the analysis of statistical data from the National Public Defender's Office Survey (2025), in order to offer empirical support that reinforces the discussion on access to justice and the effectiveness of consensual methods of conflict resolution. The results indicate that the Public Defender's Office's actions have expanded with the support of norms such as the CPC/2015 and LC No. 132/2009, promoting extrajudicial solutions that reduce litigation and relieve the burden on the Judiciary. The adoption of self-composition methods has proven effective for social pacification and the reduction of procedural costs. In conclusion, it is argued that strengthening the Public Defender's Office and consensual mechanisms represents decisive measures to promote legal certainty, reduce costs and the duration of proceedings, foster social pacification, and promote the effective inclusion of vulnerable groups, with positive impacts on the economic environment.DOI: https://doi.org/10.56238/sevened2025.040-013